SOLID DISPERSIONS: A METHOD TO IMPROVE BIOAVAILABILITY OF ORAL DRUG DOSAGE FORM - Puri, Ritika; Bhatti, Manisha (Journal of Biomedical and Pharmaceutical Research, 2019)
Presently only few percent of drugs having high aqueous solubility, Number of drugs are belonging to biopharmaceutical classification system class II that means possessing poor aqueous solubility eventually results in low level of drug in systemic circulation. To overcome this problem, various strategies have been come out into notion such as self emulsifying drug delivery system solid dispersions, use of surface active agents, complex formation. Solid dispersions is found to be promising approach to increase bioavailability by use of various polymers. This review focuses on the mechanism of drug release from solid dispersion with its method of preparation and applications. Key words: dissolution, particle size, solid dispersion